The P gene of bovine parainfluenza virus 3 expresses all three reading frames from a single mRNA editing site. - Pelet, T (1991)
The P gene of bovine parainfluenza virus 3 (bPIV3) contains two downstream overlapping ORFs, called V and D. By comparison with the mRNA editing sites of other paramyxoviruses, two editing sites were predicted for bPIV3; site a to express the D protein, and site b to express the V protein. Examination of the bPIV3 mRNAs, however, indicates that site b is non-functional whereas site a operates frequently. Insertions at site a give rise to both V and D protein mRNAs, because a very broad distribution of Gs is added when insertions occur. This broad distribution is very different from the editing sites of Sendai virus or SV5, where predominantly one form of edited mRNA containing either a one or two G insertion respectively is created, to access the single overlapping ORF of these viruses. A model is proposed to explain how paramyxoviruses control the range of G insertions on that fraction of the mRNAs where insertions occur. The bPIV3 P gene is unique as far as we know, in that a sizeable portion of the gene expresses all 3 reading frames as protein. bPIV3 apparently does this from a single editing site by removing the constraints which control the number of slippage rounds which take place.